Role models that make you unhappy: Light paternalism, social learning and welfare - Christian Cordes; Christian Schubert (Max Planck Institute of Economics, 2010)
Behavioral (e.g. consumption) patterns of boundedly rational agents can lead these agents into learning dynamics that appear to be wasteful in terms of well-being or welfare. Within settings displaying preference endogeneity, it is however still unclear how to conceptualize well-being. This paper contributes to the discussion by suggesting a formal model of preference learning that can inform the construction of alternative notions of dynamic well-being. Based on the assumption that interacting agents are subject to two biases that make them systematically prefer some cultural variants over others, a procedural notion of well-being can be developed, based on the idea that policy should identify and confine conditions that generate dynamic instability in preference trajectories.
urn:nbn:de:gbv:27-20110630-110118-0
Keywords: D63; O12; D11; D83; C61; 330; Social Learning; Preference Change; Welfare; Human Cognition; Consumer Behavior; Konsumentenverhalten; Lernprozess; Präferenztheorie; Beschränkte Rationalität; Kognition; Lebensqualität; Zufriedenheit; Theorie